Comparison of abdominal obesity by waist-to-height ratio and waist circumference among Congolese adults in the Gombe Matadi Health Zone in 2019 - Palmich Nzau; Bernard-Kennedy Nkongolo; Steve Botomba; Marie-claire Muyer Muel Telo (Journal of Global Health Economics and Policy, 2025)
# Background Abdominal obesity is a strong predictor of cardiometabolic risk. Although precise measurements exist, waist circumference (WC) and waist-to-height ratio (WHtR) are widely accessible and inexpensive indicators. This study evaluated the level of agreement between WC and WHtR in identifying abdominal obesity among Congolese adults in the Gombe Matadi Health Zone. # Methods A secondary analysis was performed using data from a 2019 cross-sectional study of 1,531 adults. A five-stage sampling method was used to select participants. We conducted a descriptive analysis, reporting frequencies and percentages, and used the Kappa coefficient to assess the agreement between WC and WHtR. # Results Of the 1,531 participants, 52.8% were female, and about 72% were aged 40 years or older. While BMI indicated a low prevalence of general obesity (3.7%), WHtR (70.6%) identified substantially more cases of abdominal obesity than WC (32.1%). Together, both measures accounted for 32% of cases. Overall, the agreement between WHtR and WC was low (kappa = 0.32). # Conclusions WC and WHtR cannot be used interchangeably to measure abdominal obesity in this Congolese population. Concurrent use of both measures is preferable to enhance detection of at-risk individuals. WHtR, in particular, shows promise as a simple and practical anthropometric index for predicting metabolic risk, and it complements WC in assessing abdominal obesity.